Impact of the rotor on FRA signatures and its implications for motor health assessment - Khan, R.; Yousof, M. F. M.; Abd-Rahman, R.; Al-Ameri, S. M.; Azis, N. (2024)
Electrical machine condition monitoring is essential in industrial processes for increasing workplace security, ensuring reliability, and cost-effective machine operation. The frequency response analysis (FRA) monitoring technique is gaining heightened popularity due to its reliability. The main purpose of this paper is to investigate the influence of the rotor on motor FRA signature. The frequency response is a highly sensitive technique. Therefore, any small defect in the motor condition will produce a unique frequency response which then can be analyzed and detected early. In this study, two motors are selected, and the corresponding frequency response is measured. To understand the impact of the rotor on the FRA signature two measurements are considered. FRA signature with and without rotor. The results obtained from both measurements are compared and analyzed. For a better understanding of the results, statistical indicators are used. The practical results are based on the measurements taken from the experimental setup